Proceedings of the ACM Web Science Conference 2015
DOI: 10.1145/2786451.2786472
|View full text |Cite
|
Sign up to set email alerts
|

Building a Social Machine

Abstract: This paper discusses the construction of a Social Machine, a socio-technical system in which people achieve new, creative goals enabled by automated processes that are handled by technology. Specifically, the Social Machine is an online TimeBank, a time-based way for people to give and receive services; it is designed for use in the context of inclusive research (initially) with people with learning disabilities.We describe the use of physical and digital (online) focus groups to gather inputs to drive the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Such an approach can be highly effective for democratising the engagement, discussion and generation of new ideas (Hooper, Nind, Parsons, Power & Collis, 2015). We promoted the online discussion among people in our various networks with an interest in issues of power, participation, user experience and accessible design to participate in informing the development of the prototype TimeBank.…”
Section: Twitter Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach can be highly effective for democratising the engagement, discussion and generation of new ideas (Hooper, Nind, Parsons, Power & Collis, 2015). We promoted the online discussion among people in our various networks with an interest in issues of power, participation, user experience and accessible design to participate in informing the development of the prototype TimeBank.…”
Section: Twitter Discussionmentioning
confidence: 99%
“…Our collaborative research has provided a strong steer on the technical requirements for the next iteration of the software to make it accessible enough for further testing with users. These are discussed in a technical paper (Hooper et al, 2015) and are not the focus here. Further design and development work is necessary for the accessibility, utility and attractiveness of the software.…”
Section: Next Stepsmentioning
confidence: 99%
“…By investigating 892 community residents' willingness and their perception of timebank in Hangzhou, Shao et al considered that we should strengthen the application of intelligent technology to enhancing the ability to meet the demand of mutual volunteer assistance for the elderly, and perfecting the timebank model to enhance the sustainable development ability of mutual volunteer service (30). In addition, Hooper et al introduced a kind of social machine, which is an online timebank and a time-based way for people with learning disabilities to give and receive services (31). For the studies on China, after summarizing the innovations of China's timebank, Chen and Huang concluded that the shortcomings of the timebank's early development mainly include narrow community coverage, the value measurement problem of specific services, the operation problem of timebank and especially the low participation of the young generation (7).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both activities contributed valuable ideas about how accessibility, online safety, trust, and reciprocity of the time exchanges could be managed, and reminded us of the need for caution in these areas. More information about the findings of these activities can be found in [11,16].…”
Section: Validating and Extending The Initial Ideamentioning
confidence: 99%
“…Our proposed solution to this problem is to inclusively co-design an online TimeBank that enables university researchers and community members to be rewarded equitably for the time they contribute to inclusive research [11]. This paper outlines the process of initiation and development of the TimeBank idea, and discusses the extent to which co-design was achievable at all stages of the project.…”
Section: Introductionmentioning
confidence: 99%